DATA PROCESSING SYSTEM, INFORMATION PROCESSING APPARATUS, PORTABLE COMMUNICATION DEVICE, CONTROL METHOD, AND PROGRAM - FUKUI AKITOMO (2024)
To provide a data processing system, an information processing apparatus, a portable communication device, a control method, and a program that can determine whether a user has approached the information processing apparatus without requiring complicated operation on the portable communication device carried by the user.SOLUTION: A data processing system 1 has a portable terminal 101 and an image forming apparatus 104 that can communicate with each other by using BLE and a UWB. The portable terminal 101 and the image forming apparatus 104 exchange communication setting information in the UWB with each other by using the BLE. When the portable terminal 101 transmits job data to the image forming apparatus 104 by using the UWB on the basis of the communication setting information, the image forming apparatus 104 sends distance measurement request data to a distance measurement target having the job data added with information, and starts distance measurement in TWR.SELECTED DRAWING: Figure 7 【課題】ユーザーが所持する携帯通信装置への煩雑な操作を要することなく、ユーザーが情報処理装置に近づいたか否かを判定できるデータ処理システム、情報処理装置、携帯通信装置、制御方法、及びプログラムを提供する。【解決手段】データ処理システム１は、ＢＬＥ及びＵＷＢにより相互に通信可能な携帯端末１０１と画像形成装置１０４とを有し、ＢＬＥを用いてＵＷＢでの通信設定情報を携帯端末１０１と画像形成装置１０４の間で相互に交換し、携帯端末１０１がその通信設定情報に基づいてＵＷＢにより画像形成装置１０４にジョブデータを送信すると、画像形成装置１０４は、そのジョブデータに情報が付加された測距対象に対して測距要求データを発信し、ＴＷＲでの測距を開始する。【選択図】図７